Bitter taste receptors on airway smooth muscle as targets for novel bronchodilators. (September 2013) - Liggett, Stephen B
<x xml:space="preserve">Abstract</x> Introduction: There is an unmet need for a new class of direct bronchodilators for the treatment of asthma and chronic obstructive lung disease. Unexpectedly, bitter taste receptors (TAS2Rs) have been localized on airway smooth muscle and when activated cause marked smooth muscle relaxation through a mechanism that is distinct from β2-adrenegic receptors. Thus TAS2R agonists have emerged as a novel class of bronchodilator. Areas covered: A synopsis of the TAS2R family and its biology for bitter taste perception on the tongue is provided, followed by a review of the identification and molecular and physiological characterization of TAS2R subtypes on human and mouse airway smooth muscle. The proposed molecular mechanisms leading to the relaxation response are provided, along with gaps in our understanding at certain points in the signaling cascade. Unresolved issues that may need to be considered for drug development are discussed. Expert opinion: TAS2R agonists show promise as a new class of highly efficacious bronchodilators for treatment of obstructive lung disease. With tens of thousands of known natural and synthetic bitter compounds, there is substantial diversity within the known agonists, and, a ready source of agents for screening and further development of an inhaled TAS2R agonist for therapeutic purposes.